STUDENT RETENTION IN A PUBLIC UNIVERSITY IN NORTHERN KAZAKHSTAN: A QUALITATIVE STUDY - Daurenbayeva, Aikerim (Nazarbayev University Graduate School of Education, 2025)
This study explores the factors influencing undergraduate student retention at a public university in Kazakhstan, focusing on second-year students from STEM and Social Sciences disciplines who considered withdrawing but ultimately decided to stay. Guided by Tinto’s framework of academic and social integration, and complemented by intrinsic and extrinsic motivation factors, the qualitative research collected data by conducting semi-structured interviews with 12 participants. The findings revealed that while academic and social integration contributed positively to students’ experiences, through a sense of personal achievement and supportive peer networks, these factors alone were not decisive in the choice to remain at the university. Instead, intrinsic motivation, such as personal interest in the field of study and commitment to long-term goals, and extrinsic influences, including familial support and career aspirations, played a more critical role in shaping students’ persistence. The study highlights the complex interplay of internal drive, academic challenges, and socio-cultural influences in the persistence decisions of students. It suggests that student retention strategies in Kazakhstani higher education should adopt a holistic approach, incorporating emotional, academic, and structural support that meet diverse student needs. The research contributes to the existing body of literature within the local higher education context and offers implications for institutional policies aimed at improving retention, student well-being, and academic success.
Keywords: student retention; academic integration; social integration; intrinsic and motivation; extrinsic motivation; higher education; Kazakhstan; student persistence; institutional support; type of access: embargo